Effects of Chk1 inhibitor or paclitaxel on cisplatin-induced cell-cycle kinetics and survival in parental and cisplatin-resistant HeLa cells expressing fluorescent ubiquitination-based cell cycle indicator (Fucci). Issue 1 (2015) - Yamada, Chisato; Kaida, Atsushi; Okuyama, Kohei; Harada, Kiyoshi; Miura, Masahiko
No abstract available